Driving Business Sustainability in Islamic Enterprises: The Role of Moral Commitment - Yusril Firmansyah Akbar; Kurniawan Ramadhani; Kiky Zulkifli (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
This study examines the role of moral commitment as a foundational determinant of business sustainability in Islamic enterprises. Amid increasing global concerns over ethical failures, environmental degradation, and social inequality, Islamic enterprises are expected to demonstrate moral integrity grounded in Islamic ethical values such as amanah (trustworthiness), adl (justice), ihsan (excellence), and maslahah (public interest). This research aims to analyze how moral commitment is conceptualized, internalized, and operationalized within Islamic business organizations and how it contributes to long-term sustainability across economic, social, and environmental dimensions. Employing a qualitative literature-based research design with a normative-philosophical and conceptual approach, this study synthesizes contemporary national and international scholarly works on Islamic business ethics and sustainability. The findings reveal that moral commitment functions not merely as a normative ideal but as a strategic organizational asset that strengthens governance, stakeholder trust, risk management, and adaptive resilience. The study contributes theoretically by integrating Islamic moral philosophy with sustainability theory and practically by offering a value-based framework for strengthening sustainable Islamic enterprises.